Decreased vitamin D serum levels at melanoma diagnosis are associated with tumor ulceration and high tumor mitotic rate. Issue 6 (December 2019) - Moreno-Arrones, Oscar M.; Zegeer, Josh; Gerbo, Michael; Manrique-Silva, Esperanza; Requena, Celia; Traves, Víctor; Nagore, Eduardo
Abstract : The aim of this study is to evaluate the relation between 25-hydroxyvitamin D levels at diagnosis and pathological characteristics in primary invasive melanoma. A cross-sectional study was designed based on a series of 204 consecutive patients diagnosed of invasive melanomas in the 2013–2017 period at a single institution. 25-hydroxyvitamin D serum levels at diagnosis were assessed, and three groups were defined by vitamin D status: deficiency, insufficiency, and sufficiency. Clinical and pathological characteristics were compared between the groups by Chi-square test. Logistic regression models were performed to evaluate the association between vitamin D status and Breslow thickness, ulceration, and tumor mitotic rate. A significant association between vitamin D levels at diagnosis and location, tumor mitotic rate, and ulceration was found; and a borderline association with Breslow thickness and BMI. Deficient levels were found in 7.8% of patients and increased the risk of presenting ulcerated tumors [odds ratio: 6.8 (95% confidence interval: 1.5–29.7; P = 0.012)] and with a tumor mitotic rate greater than 1 mitosis/mm 2 [odds ratio: 6.0 (95% confidence interval: 1.4–25.1; P = 0.014)]. A marginal increased risk of tumor thickness greater than 1 mm was also observed [odds ratio: 3.7 (95% confidence interval: 1.0–13.9; P = 0.057)]. Our study suggests a role of vitamin D levels in melanoma aggressiveness and raises the question as to whether vitamin D levels should be monitored, or even supplemented, in people with low yearly sun exposure.